Variable impedance interaction and demonstration interface design based on measurement of arm muscle co-activation for demonstration learning. (May 2019) - Wu, Rui; Zhang, He; Peng, Tao; Fu, Le; Zhao, Jie
Highlights: Human's intention and muscle activity can be used to change impedance gain of robots. Tutors can change robots' performance intuitively and conveniently by our interface. Using our interface can help tutor to do complex interaction and demonstration tasks. Tutors who use our interface can save energy and improve efficiency during tasks. Both trajectory and impedance gain of tutors can be recorded and learned by robots. Abstract: Learning from Demonstration (LfD) is a good way for robots to learn some complex tasks from human tutors, but the ordinary demonstration mode of LfD is unsuitable for learning interaction tasks that require the robot to run under the variable impedance control mode. In this study, we develop a variable impedance physical human–robot interaction (pHRI) interface and LfD mode for human motion skill transport based on surface electromyography (sEMG) signal and kinesthetic teaching. The pHRI interface and LfD mode developed in this study have the following advantages: 1) they can provide intuitive and pleasing variable impedance interaction effect for kinesthetic teaching on the basis of human arm stiffness estimation using sEMG signal. 2) They can simultaneously provide the expected motion data (expected end-effector trajectory and impedance gain scheduling) of tutors for demonstration learning, and these motion data can be used for learning complex interaction tasks under robot variable impedance control mode. 3) Kinesthetic teaching can provide tutor haptic feedback, which conforms to the human–human teaching mode, thereby reducing professional knowledge requirements and energy consumption of the tutor and improving teaching effect and efficiency. The pHRI interface and LfD mode are experimentally tested by two interaction and demonstration experiments. Results show that the proposed interface and mode have better dynamic interaction characteristic and performance than the constant impedance gain control LfD mode. Moreover, the tutor can be rapidly familiarized with this interface and mode and finish the demonstration with low energy consumption.